Organisational Development and Governance of the National Statistical System - Strode, Mary (World Bank, Washington, DC, 2013)
This report looks at the governance and management systems required to establish the National Statistical System, and is the result of two missions to South Africa by the consultant. The development of the National Statistical System (NSS) has made considerable progress over the life of the project particularly in raising awareness of the NSS among all parts of government, and forming partnerships with producer and user government bodies. Several consultants have worked on plans for the NSS, including a business plan, departmental audits and training. A step change in data quality in the wider statistical system of government departments will require an increase in resources and greater priority to be given to improving information systems. Additional resources will be required in the producing departments outside Statistics South Africa (Stats SA).